AN OVERVIEW ON THE ECOLOGY OF VARANID LIZARDS - Evy - Arida (ZOO INDONESIA, 2008)
Arida, E. 2008. An overview on the ecology of Varanid lizards. Zoo Indonesia 17(2):67-82. Body size is a morphological character that can be useful to estimate the sizeof home range in varanids. It may also be used to cue for habitat type and mode of lifeof varanid lizards. Nevertheless, although body size may be a good predictor ofhome range size, it may not be useful to infer population density, because nonterritorialitynature of varanid lizards generates home range overlaps. Although nonterritorialitynature may hinder inference of population density, it can signal for highdensity through the signature of aggression. However, the magnitude of density itselfwould not be well quantified. An approach to population density estimation is the useof reproductive biology data. Reproductive biology data of wild varanids can be usedto base a projection on population trends. Despite the notion, data on reproductionfrom wild populations seems to be scarce, especially from some regions in Asia.Regular population monitoring for general census and reproductive status is definitelystill needed to allow for sound estimates of population density and its dynamics.